IMPLEMENTASI MEDIA DESAIN KOMUNIKASI VISUAL UNTUK MEMBANTU PROMOSI USAHA JASA SUANDA BALI DRIVER GUIDE - I Nyoman Agus Suarya Putra; I Nyoman Artika; Ni Wayan Wardani (Sewagati, 2026)
This community service aims to develop the visual identity and promotional media for the micro-enterprise "Suanda Bali Driver Guide", located in Gianyar, Bali. The main problem faced by the partner is the lack of optimal digital promotion, as well as the absence of a logo, trademark, and a professional video profile. The urgency of this research is to increase brand awareness and market reach amidst the highly competitive tourism industry. The method implemented includes identification, data analysis, visual communication design (pre-production, production, and post-production), and evaluation. The result of this activity is the creation of a brand logo and a 10 minute promotional video edited using Adobe Premiere CC. The outputs are designed based on visual communication principles to highlight the partner's unique local culture and excellent service. In conclusion, implementing strategic digital marketing and visual design significantly supports the business development, professional image, and economic growth of the tourism transportation service.